2017
DOI: 10.1016/j.ijrobp.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Radiation Oncologists on the Early Adoption of Hypofractionated Radiation Therapy for Early-Stage Breast Cancer

Abstract: SummaryThis study evaluated the impact of radiation oncologists on the early adoption of hypofractionated radiation therapy for early-stage breast cancer. Using SEERMedicare data and multilevel, multivariable logistic models, we assessed the impact of radiation oncologist and geographic practice area on the likelihood of receiving hypofractionated radiation therapy. The key finding of our study was that the individual radiation oncologist heavily influenced the decision to pursue hypofractionation.Purpose: Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 50 publications
1
29
1
Order By: Relevance
“…Although not as strongly suggested as in other studies, the impact of individual clinician's practice pattern remained a significant predictor of the HF‐WBRT adoption in our study. In several US centres, implementation of clinical directives and peer‐reviewed chart‐rounds (as a mean of negating individual clinician's perception towards HF‐WBRT) have resulted in a significant increase in the HF‐WBRT adoption .…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Although not as strongly suggested as in other studies, the impact of individual clinician's practice pattern remained a significant predictor of the HF‐WBRT adoption in our study. In several US centres, implementation of clinical directives and peer‐reviewed chart‐rounds (as a mean of negating individual clinician's perception towards HF‐WBRT) have resulted in a significant increase in the HF‐WBRT adoption .…”
Section: Discussioncontrasting
confidence: 81%
“…While the HF‐WBRT adoption rate clearly increased over time and was largely reflective of the sequential publications of high‐level clinical evidence, mainstreaming of HF‐WBRT into clinical practice as the preferred fractionation regimen for early‐stage breast cancer patients required a prolonged period of adjustment for the clinicians. As postulated in the earlier studies, this lag may reflect the clinicians’ reservation in treatment de‐escalation and caution in extrapolating the data beyond the guideline‐endorsed criteria. Our results found that the delivery of chemotherapy and/or TBBR, and larger CWSD negatively predicted for HF‐WBRT prescription, even after the random clinician effect was adjusted for.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…If approved, CMS enters into a Data Use Agreement (DUA) with the researcher. These data have been used to describe patterns of morbidity2 and mortality3 and burden of disease,4,5 compare the effectiveness of pharmacologic therapies,6–9 examine the cost of care,1013 evaluate the effects of provider practices on the delivery of care,1417 and explore the effects of important policy changes on physician practices and patient outcomes 1823. The use of the Medicare databases as sources for epidemiologic and health outcomes research has increased substantially over time (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The UK and Canada have seen far broader adoption of HF-WBI (around 80% and 71%, respectively) (18,19), which can in part be attributed to the UK’s nationalized adoption of HF-WBI and Canada’s more flexible use of fee-for-service payments. It is estimated that a US hospital-based practice’s adoption of a 70% HF-WBI rate would result in annual reductions of $300,790 in technical revenues and 731 professional RVUs with current reimbursement policies (20), representing significant proportions of total practice income; therefore, it is not surprising that variation in HF-WBI utilization has been found to be related more to individual provider characteristics than clinical or demographic characteristics (21). …”
mentioning
confidence: 99%